THE FUNDAMENTAL SOLUTIONS OF DIFFERENTIAL OPERATOR WITH BLOCK - TRIANGULAR OPERATOR COEFFICIENTS - Kholkin, A (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
For the non-selfadjoint Sturm-Liouville equation with a block-triangular operator potential that increases at infinity, both increasing and decreasing at infinity operator solutions are found. The asymptotics of these solutions at infinity is defined.